Functional genetic variability at promoters of pro‐(IL‐18) and anti‐(IL‐10) inflammatory affects their mRNA expression and survival in prostate carcinoma patients: Five year follow‐up study. Issue 15 (17th August 2015) - Dwivedi, Shailendra; Goel, Apul; Mandhani, Anil; Khattri, Sanjay; Sharma, Praveen; Misra, Sanjeev; Pant, Kamlesh Kumar
<x xml:space="preserve">Abstract</x> BACKGROUND Inflammation is an important hallmark of all cancers. The net inflammatory response is determined by a delicate balance between pro‐ and anti‐inflammatory cytokines, which, in turn, is determined by the genetic make‐up. The present study investigates the role of variations in the promoter regions of IL‐18 and IL‐10 (anti‐inflammatory) cytokines on mRNA expressions and survival in prostate cancer (PCa) patients. METHODS The study was conducted on 584 volunteer males (291 patients of PCa, between 40–80 years of age. Genetic variants were studied by using RFLP and confirmed by probe based method. Expressions of mRNA were evaluated by real‐time PCR (Roche light cycler 480). Relative mRNA and fold change gene expressions were analyzed by ([1/2] ΔCt) and (2‐ΔΔCt) methods, respectively, and 5 year follow‐ups were evaluated by Log‐rank (Mantel–Cox) test with Log‐rank test for trends. RESULTS IL‐18 mRNA expression was significantly elevated in GG genotypes (at −137) of PCa with relative mRNA expression of 13.95, that is, 8.48 folds higher (P < 0.05) than controls; and showed a significant median survival of 1243 days. The CC genotypes of IL‐10 at both loci (−819 T/C and −592C/A) showed 3.63 and 3.52 higher relative mRNA expressions than controls, but poor survival of 984 and 1052 days than TT of 1359 days and AA of 1371 days. CONCLUSIONS Genetic variants of pro‐inflammatory IL‐18 which showed higher relative mRNA expressions have better survival. Genetic variants of anti‐inflammatory IL‐10 with higher relative mRNA expression showed decreased chances of survival. Prostate 75:1737–1746, 2015. © 2015 Wiley Periodicals, Inc.